Ultrasonic cavitation assisted solvothermal synthesis of superparamagnetic zinc ferrite nanoparticles - Sireenart Surinwong (2018)
Nanoparticles of cubic zinc ferrites (Fd3̄m, a = 8.41(3)-8.44(1) Å) were synthesized as a single phase by an ultrasonic cavitation-assisted solvothermal technique using ethyl alcohol-water mixed solvents at temperatures of 150 C or higher for 18 h or more. The influences of the ultrasonic cavitation and the use of C2H5OH-H2O mixed solvents in diminishing average particle size and in improving particle size uniformity were illustrated. The largest average size of nanoparticles obtained was 20 nm as measured from SEM photographs, with crystallite size of approximately 10 nm as estimated from XRD results. The room-temperature field-dependent magnetization of the nanoparticles obtained showed a characteristic S feature with magnetization of 24.32 emu/g at 1 T. © 2012 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences.